Speech Act Of Refusal On Vertical Line Levels In Japanese And Indian Cultures - Ninik Elika; Oktiva Herry Chandra (Green Publisher Indonesia, 2024)
This study aims to describe the refusal speech acts of Japanese and Indian people in the context of vertical relationship lines. The research employs a cross-cultural pragmatic approach with a qualitative descriptive paradigm method. Data collection was carried out using the Discourse Completion Task (DCT) method on native Japanese and Indian speakers. Data were analyzed using Brown and Levinson's politeness theory and Ochi Suzuki's refusal strategies, presented through a descriptive analysis model. The results indicate differences in the refusal speech acts of Japanese and Indian people within vertical relationship lines. Japanese people, in this context, tend to use indirect refusals, employing various methods to show respect and avoid offending the interlocutor. This is influenced by factors such as social status, social distance, kinship relations, and the speaker's age. Indirect refusals often involve expressions of apology and the use of different language forms. There are slight differences between male and female refusal speech acts in Japanese culture. Women are more careful in choosing words to refuse, showing a higher regard for the feelings of the speaker. In contrast, Japanese men tend to provide straightforward reasons for their refusals but still choose their words cautiously. In the case of Indian people within vertical relationship lines, the majority use direct refusals, as evidenced by their speech. Social factors such as social status and social distance also play a role. Both Indian men and women tend to deliver refusals straightforwardly, assertively, and directly (to the point).